Evolutionary Dynamics of Non-Coding Regions in Pancreatic Ductal Adenocarcinoma - Hayashi, Akimasa; Yu-Jui, Ho; Makohon-Moore, Alvin P; Zucker, Amanda; Hong, Jungeui; Reiter, Johannes G; Huang, Jinlong; Zhang, Lance; Attiyeh, Marc A; Baez, Priscilla; Kappagantula, Rajya; Melchor, Jerry P; et al. (bioRxiv, 2020)
Abstract While the non-coding genome appears to play a role, the dynamic nature of noncoding alterations with respect to clonal progression of solid tumors remains unexplored. To address this gap in knowledge we performed multiregional whole genome sequencing and clonal analysis to elucidate the evolutionary dynamics of non-coding regions in pancreatic cancer relative to those of the coding genome. We find that the mutational burden of noncoding DNA is higher than coding DNA. However, when noncoding DNA was segregated into enhancer and non-enhancer regions, enhancers were more similar to coding DNA. Mutational signatures of noncoding and coding DNA further revealed the similar mutational spectra of enhancers to coding DNA whereas the mutational spectra of non-enhancer, noncoding DNA had an entirely different pattern. These findings shed light on the role of noncoding DNA in pancreatic cancer. Competing Interest Statement EMOR has research funding to MSK from Celgene/BMS, BioNTech, ActaBiologica, AstraZenica, Silenseed, Arcus and Gossamer and is a consult to Merck, Cytomx, BioLineRx, Targovax, Celgene/BMS and Loxo, Polaris and Rafael. All authors declare no competing interests.